Influence of different light intensities on cercarial emergence of Schistosoma Japonicum (Philippine Strain) from Oncomelania Hupensis Quadrasi - Claveria, Florencia G. (1988)
The filter disc plate method of antibiotic assay was tested for the assay of aflatoxin using Bacillus megaterium and B. thuringiensis spores. Significants inhibitions were obtained on the growth of both tests organisms with positive linear correlation between aflatoxin concentration and zones of inhibition. The responses of the test organisms to aflatoxin were not significantly different.
Laboratory-reared male and female Oncomelania hupensis quadrasi (12-15 wks old) were exposed to 3-5 miracidia of Schistosoma japonicum. Forty to forty-eight male and female infected snails were subjected to different intensities of artificial illumination (183-503 lux from two-40 watt fluorescent bulb source), and their cercarial production was monitored at the 14th, 16th, 18th, and 20th wk post-exposure (PE) for four consecutive days. Infected snails that produced cercariae were highest among those exposed to 183-305 lux. Mean cercarial emergence from those exposed to 183-244 lux ranged from 48-62 cercariae per snail per four days. A significantly lower cercarial emergence was recorded at 16th wk PE, and at the 18th and 20th wk PE there was complete cessation of cercarial emergence. Optimum water temperature that stimulated higher cercarial releases ranged from 26-30 deg C. Despite continuous use of artificial illumination, cercarial emergence remained periodic (i.e. 24-20 h interval) and nocturnal with emergence occurring during the late afternoon and early morning hours. Minimum requirements of submergence in water prior to initial non-periodic emergence was six hours. The decrease in cercarial emergence and diminished motility of snails at higher temperatures suggest that cercarial emergence is apparently and directly influenced by water temperature and secondarily, by light intensity and periodicity.
Includes bibliographical references (pages 371-372)
Keywords: Biochemistry; Schistosoma Japonicum(Philippine Strain).; Oncomelania Hupensis Quadrasi; Articial illumination; Snails